Antidiabetic and antihyperlipidemic effects of crude fractions from Chlorophytum borivilianum root methanolic extract on streptozotocin induced diabetic rats and phytochemical investigation by LCMS analysis. - Vikhe, Sunayana; Aladi, Pravin; Vikhe, Rahul Laxman (International Journal of Experimental Research and Review, 2024)
To evaluate the in vitro and in vivo pharmacological efficacy of the plant Chlorophytum borivilianum in diabetes and hyperlipidemia and to confine and describe the synthetic constituents from the roots that are in charge of the action. The present study was carried out to investigate the ethno-medical use of Chlorophytum borivilianum root methanolic extract as a potential anti-diabetic and antihyperlipidemic agent in STZ-induced diabetic rats. Extract was tested for in vitro and in vivo biological activities. Soxhlet extraction was carried out using methanol as a solvent, and TLC and column chromatography were used for fractionation. Liquid Chromatography and Mass Spectroscopic study confirmed the structures of isolated compounds. Chlorophytum borivilianum root methanolic extract showed the presence of phytoconstituents as Dihydrocapsaicin, Reserpine, Deserpidine, Biliverdin-IX-?, and Cassiamin C having a therapeutic effect. Dihydrocapsaicin was identified at RT 7.572 and the Chlorophytum borivilianum root chloroform methanolic extract fraction noticeably depleted increased blood glucose levels and had positive effects on altered lipid profile after administering a dose of 150 mg/kg orally compared with oral hypoglycemic drug metformin. All the results are dose-dependent. Active chloroform-methanol fraction from methanol extract showed the presence of anti-diabetic compound, Dihydrocapsaicin. The chloroform-methanol fraction from the methanolic extract of Chlorophytum borivilianum root can inhibit the parameters linked to diabetes and hyperlipidemia.